Hegel and contemporary practical philosophy: beyond Kantian constructivism - Gledhill, James; Stein, Sebastian (Routledge, Taylor & Francis Group, 2020)
"While Kantian constructivism has become one of the most influential and systematic schools of thought in analytic moral and political philosophy, Hegelian approaches to practical normativity hold out the promise of building upon Kantian insights into individual self-determination while avoiding their dualistic tendencies. James Gledhill and Sebastian Stein unite distinguished scholars of German idealism and contemporary Anglophone practical philosophy with rising stars in the field, to explore whether Hegelian idealist philosophy can offer the categories that analytic practical philosophy requires to overcome the contradictions that have so far plagued Kantian constructivism. The volume organizes the contributions into three parts. The first of these engages debates in metaethics regarding the relationship between realism and constructivism. The second part sees contributors draw on debates about the nature of political normativity, focusing primarily on the problems of historical contextualism, relativism and critical reflection. The concluding part considers the application of the Hegelian framework to contemporary debates about specific ethical issues, including multiculturalism, democracy and human rights. Hegel and Contemporary Practical Philosophy contributes to the on-going debate about the importance of systematic philosophy in the context of practical philosophy, engages with contemporary discussions about the shape of a rational social order, and gauges the timeliness of Hegelian philosophy. This book is a must read to scholars interested in Hegel and in the contemporary tradition of Kantian constructivism in moral and political philosophy"--
Includes bibliographical references and index
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Aufsatzsammlung; Konstruktivismus; Kantianismus; Ethik; Praktische Philosophie; Hegel, Georg Wilhelm Friedrich